1979
DOI: 10.1021/bi00593a005
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism study of the solution conformation of luteinizing hormone releasing hormone

Abstract: A systematic investigation has been made into the circular dichroic behavior of luteinizing hormone releasing hormone and its peptide fragments and deletion analogues. The results are interpreted to mean that the hormone exists in solution as an ensemble of conformers with different sensitivities to temperature and solvent composition. The far-ultraviolet circular dichroic spectra exhibited by the hormone under different experimental conditions can be simulated satisfactorily by the weighted addition of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…A number of studies have appeared on the CD of LHRH in both aqueous and organic media (Mabrey & Klotz, 1976;Cann et al, 1979). The «-factor from S. cerevisiae activates mammalian gonadotrophs (Loumaye et al, 1982), and several investigators have suggested structural similarities between LHRH and the yeast mating pheromone (Geiger, 1978;Kitada et al, 1979;Stewart et al, 1979).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have appeared on the CD of LHRH in both aqueous and organic media (Mabrey & Klotz, 1976;Cann et al, 1979). The «-factor from S. cerevisiae activates mammalian gonadotrophs (Loumaye et al, 1982), and several investigators have suggested structural similarities between LHRH and the yeast mating pheromone (Geiger, 1978;Kitada et al, 1979;Stewart et al, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…The «-factor from S. cerevisiae activates mammalian gonadotrophs (Loumaye et al, 1982), and several investigators have suggested structural similarities between LHRH and the yeast mating pheromone (Geiger, 1978;Kitada et al, 1979;Stewart et al, 1979). In view of this homology, it is pertinent that the CD of LHRH in water is characterized by a weak positive maximum at 220 nm and a strong minimum at around 200-205 nm (Cann et al, 1979). A systematic investigation of LHRH concluded that this peptide exists as an ensemble of structures in both trifluoroethanol and water and that the far-ultraviolet CD spectra can be simulated by the spectra of its aliphatic-and aromatic-containing halves.…”
Section: Resultsmentioning
confidence: 99%
“…The weak bands around 2 8 0 and 290 nm in GnRH arising from asymmetrically placed Tyr and Trp residues, respectively, as observed earlier by Cann et ul. (12) became more positive on CaZ+ addition (data not shown). These changes were relatively small in magnitude.…”
Section: Spectral Changes On Ca2+ Bindingmentioning
confidence: 87%
“…As a prerequisite to understanding of GnRH action and design of potent agonists and antagonists for therapeutic use, much effort has been directed toward the elucidation of the conformation of the hormone and its analogs and relating this information to the observed biological activities of these analogs. Spectroscopic data including circular dichroism (CD) (12) and nuclear magnetic resonance (NMR) (13)(14)(15) ) have indicated a highly flexible conformation for GnRH in water and other polar solvents whereas, in nonpolar solvents such as trifluoroethanol (TFE), the presence of ordered structures has been detected by CD (16,17). Theoretical computations of GnRH structure (11,(18)(19)(20) have identified a type 11' p-turn in the middle region (Tyrj-Gly6-Leu7-Arg') of the hormone and have implicated this conformation as a requirement for receptor binding.…”
mentioning
confidence: 99%
“…However, these analogues did not yield maximal persistent signal after photoactivation, suggesting either incomplete photoaffinity labeling or nonoptimal spatial arrangement of the covalently bound hormone. Conformational studies (Donzel et al, 1977;Cann et al, 1979;Bello et al, 1981;Kopple, 1981), conformational modeling based on energy calculations (Momany, 1976(Momany, , 1978, and structure-activity studies with GnRH (Sandow et al, 1978;Morley, 1980;Rivier et al, 1981; Karten & Rivier, 1986) suggested that the spatial interaction between GnRH and its receptor requires the Nand C-terminal segments of the decapeptide, while the middle of the sequence is held away from the receptor (Momany et al, 1977). This view was further supported by the full gonadotropin-releasing activity of GnRH analogues substituted by different macromolecules, significantly larger than the decapeptide, via side chains of D-amino acids in position 6.…”
mentioning
confidence: 99%